Efficacy and Safety of Tongxinluo Capsule as Adjunctive Treatment for Unstable Angina Pectoris: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Li, Pengqi; Xin, Qiqi; Hui, Jiaqi; Yuan, Rong; Wang, Ya; Miao, Yu; Lee, Simon Ming-Yuen; Leng, Sean X.; Cong, Weihong; , BPNMI Consortium (Frontiers in Pharmacology, 2021)
Tongxinluo capsule (TXLC) is a commonly used Chinese medicine for unstable angina pectoris (UA). This article aimed to clarify the safety and efficacy of TXLC as an adjunctive treatment for UA. Two reviewers searched 7 databases from inception to August 2021, and performed literature screening and information extraction independently. The meta-analysis was implemented after evaluating the methodological quality of each randomized controlled trial (RCT) by the Cochrane Risk of Bias tool. Sensitivity analyses were conducted for testing the stability of the results, and the Begg and Egger tests were performed for any potential publication bias. After eligibility assessment, 42 RCTs with a total of 5,421 participants were included. Evidence showed that TXLC reduced the rate of cardiovascular events [RR = 0.29, 95% CI (0.19, 0.45), p < 0.00001, I2 = 0%] {including cardiovascular mortality [RR = 0.16, 95% CI (0.03, 0.88), p = 0.03, I2 = 20%], the incidence of acute myocardial infarction [RR = 0.27, 95% CI (0.13, 0.57), p = 0.0006, I2 = 0%] and the occurrence of revascularization [RR = 0.28, 95% CI (0.15,0.54), p = 0.0001, I2 = 0%]}, all-cause mortality [RR = 0.25, 95% CI (0.06, 0.99), p = 0.05, I2 = 19%], recurrence of angina [RR = 0.25, 95% CI (0.11, 0.61), p = 0.002, I2 = 0%], the number of ST-segment depression [MD = −0.45, 95% CI (−0.69, −0.20), p = 0.0005, I2 = 0%], the summation of ST-segment depression [MD = −0.70, 95% CI (−1.08, −0.32), p = 0.0003, I2 = 70%] and the hypersensitive C-reactive protein level [MD = −2.86, 95% CI (−3.73, −1.99), p < 0.00001, I2 = 86%], increased the nitric oxide level [MD = 11.67, 95% CI (8.33, 15.02), p < 0.00001, I2 = 33%], improved the electrocardiogram change [RR = 1.23, 95% CI (1.16, 1.30), p < 0.00001, I2 = 0%] and the clinical efficacy in UA [RR = 1.26, 95% CI (1.21, 1.32), p < 0.00001, I2 = 24%], and relieved the symptoms of angina pectoris {including chest pain or tightness [RR = 1.13, 95% CI (0.97, 1.32), p = 0.12, I2 = 30%], palpitations [RR = 1.47, 95% CI (1.18, 1.84), p = 0.0007, I2 = 0%], shortness of breath [RR = 1.53, 95% CI (1.24, 1.88), p < 0.0001, I2 = 0%], and asthenia [RR = 1.69, 95% CI (0.83, 3.43), p = 0.15, I2 = 90%]}. The most common adverse effect was gastrointestinal symptoms which could be relieved and eliminated through dose reduction, medication time adjustment and symptomatic remedy. Collectively, TXLC was effective and considerably safe for UA. However, due to the unavoidable risk of bias, these results must be interpreted with caution and further verified by large-scale and high-quality RCTs. Systematic Review Registration:www.crd.york.ac.uk/PROSPERO/, identifier CRD42021232771.